PENGEMBANGAN ARSITEKTUR TERTANAM IOT UNTUK EVALUASI ABRASI PIN-ON-DISC - Rizky Muflih; Satrio Adhiyatama Erlangga; Nanang Fajar Untoro; RR Nur Assifaa (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2026)
Brake pads are crucial elements in vehicle braking systems, requiring wear assessment to ensure safety and braking efficacy. The pin-on-disc methodology is extensively used to investigate the tribological properties of various materials. However, most existing testing equipment still relies on semi-manual data logging, thus lacking the capability to provide real-time information regarding the testing parameters. Furthermore, previous investigations have mostly concentrated on examining the wear and friction coefficients of materials, while the utilization of the Internet of Things (IoT) for monitoring compressive forces remains underexplored. This study attempts to build an IoT-oriented embedded system architecture using an Arduino ATmega 2560 along with a load cell sensor to facilitate real-time monitoring of compressive forces during pin-on-disc testing. The research methodology includes system design, sensor integration, calibration, Arduino programming, and experiments at rotational speeds of 30 rpm and 40 rpm with an applied pressure of 0.2 MPa under dry, water-lubricated, and oil-lubricated conditions. Experimental findings show average compressive loads in dry conditions of 3.5668 kg and 3.1468 kg, in water lubrication conditions of 2.5750 kg and 3.1687 kg, and in oil lubrication conditions of 2.9481 kg and 4.1578 kg. The findings reveal that rotational speed and lubrication conditions affect the contact force characteristics. The originality of this investigation stems from the integration of load cells, Arduino ATmega 2560, and IoT technology for real-time monitoring of compressive forces, while its contribution lies in improving the precision and efficiency of wear testing through continuous digital data acquisition.